APAKAH KUALITAS LABA BERBASIS AKUNTANSI BERKONTRIBUSI TERHADAP MARKET OUTCOMES? - Khafid, Muhammad; Mukhibad, Hasan (University of Merdeka Malang, 2016)
AbstractThe purpose of this study was to analyze the effect of quality accrual, earnings persistence, and earnings predictability to market outcomes.The population in this study are all companies listed on the Indonesian Stock Exchange (BEI), 430 companies. The samples were 233 companies which were determined by purposive sampling technique. Data collection method used is the documentation. Data analysis technique used is multiple regression analysis. The study also tested the classical assumption consisting of: multicollinearity, linearity, heteroscedasticity and residual normality.The study states that earnings predictability variables (sig. 0,000) and earnings persistence (sig. 0.004) significantly affect market outcomes, while the accrual of variable quality not significantly affect market outcomes at the level of 0.05. The research model successfully explains the variation of the dependent variable to 14.2% (adjusted R2 value). Research in the future necessary to find an alternative measurement of the accrual quality and enhance the research model can improve the ability to explain the dependent variable.